PENGARUH PERMAINAN KALUNG ANGKA TERHADAP KEMAMPUAN MENGENAL LAMBANG BILANGAN ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 2 PEKANBARU - Indarto, Wusono; ', Dinayumalini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to find out The Effect of Numerial Necklaces Game On The Ability In Recognizing Numerals of 5-6 Year-old Students of TK Negeri Pembina 2 Pekanbaru. The population and the sample of the research are the 5-6 year-old students from group B1 in the amount of 20 at TK Negeri Pembina 2 Pekanbaru. The data collection technique used in this research is an observation. The method used is an experimental approach, that is a research which determines the effect of another variable under very strict-controlled conditions. The data analysis technique used are using scale trial and statistical method analysis through SPSS windows ver 18 program. It is obtained the t-count 50,809 with significant level of 0,000, and the t-table is 1,729 with significant level of 5% (2-tailed). Therefore, it is found t-count is (50,809) > t-table (1,729) or the significant level (0,000 < 0,05). It can be inferred that there is a significant difference of the result between pretest and posttest. Based on the obtained hypothesis result, there is an effect of numerals of 5-6 year-old students of TK Negeri Pembina 2 Pekanbaru. It can be seen from the correlation coefficient (r) in the amount of 0,989. It means the effect of numerial necklaces game on the studentsâ€™ ability in recognizing numerals is 98%, which is including into â€œvery strongâ€ level.Keywords: The Ability In Recognizing Numerals, Numerial Necklaces Game.